2016
DOI: 10.1007/s10103-016-1916-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of pulsed wave LLLT on tibial diaphysis in two rat models of experimental osteoporosis, as examined by stereological and real-time PCR gene expression analyses

Abstract: Osteoporosis (OP) and osteoporotic fracture are major public health issues for society; the burden for the affected individual is also high. Previous studies have shown that pulsed wave low-level laser therapy (PW LLLT) has osteogenic effects. This study intended to evaluate the impacts of PW LLLT on the cortical bone of osteoporotic rats' tibias in two experimental models, ovariectomized and dexamethasone-treated. We divided the rats into four ovariectomized induced OP (OVX-d) and four dexamethasone-treated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
1
21
0
1
Order By: Relevance
“…However, some recent studies show that LLLT alone is not effective in reversing the detrimental effects of OP in vivo …”
Section: Introductionmentioning
confidence: 99%
“…However, some recent studies show that LLLT alone is not effective in reversing the detrimental effects of OP in vivo …”
Section: Introductionmentioning
confidence: 99%
“…Healthy lighting needs to take into account spectral regions outside the visible range, which have physiological and psychological impacts on humans, such as infrared radiation (IR), that is present in daylight but not white light-emitting LEDs [25] . Previous studies have demonstrated the potential value of infrared radiation from laser light in the prevention of bone loss in animal models [26,27] or in elderly osteoporosis patients [28] . These studies suggest that IR supplementation to white LEDs may be bene cial in creating an arti cial lighting environment conducive to the maintenance of bone health.…”
Section: Discussionmentioning
confidence: 99%
“…The ΣP is estimated using the point-counting method. 20,21 The a/p stands for the area associated with each point projected on the limb bud. A sample of H&E staining with a point-counting grid is presented in Figure 1.…”
Section: Histological and Stereological Studiesmentioning
confidence: 99%